Culture in Language Teaching - Kovács Gabriella (Acta Universitatis Sapientiae: Philologica, 2017)
Learning a language means also the study of a different culture. This study focuses on the introduction of the topic of culture in language teaching into the curriculum of the subject Language Teaching Methodology for teacher trainees studying at Translation And Interpreting Studies, Sapientia Hungarian University of Transylvania, Faculty of Technical and Human Sciences, Târgu-Mureş. This topic has not been treated separately so far, it has only been discussed implicitly, included in other topics. But we believe that future teachers should have a more thorough theoretical and practical training in terms of what incorporating culture into language teaching implies. For this purpose, we are going to examine and discuss some of the recommendations and principles stated in the specialized literature regarding culture in foreign language teaching and reflect on what the ideal content of a course related to the teaching of this skill should be.